2019
DOI: 10.1098/rsos.181254
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between wear formation and large-particle motion in a pipe bend

Abstract: Fine and large particles flowing through a bend in a pipe move differently and therefore erode the pipe differently. This paper simulates solid–liquid two-phase flow containing large particles in a bend and analyses the relationship between the wear formation and particle motion. Wear experiments are carried out using 3-mm glass bead particles at a mass concentration of 1–15%. At the same time, the flow field and the motion of the granular system are obtained in computational fluid dynamics–discrete element me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…This phenomenon occurs in both simulations and experiments. With further observation of the wear on the wall of the hub, we found that the wear surface had corrugated stripes, which were very similar to the striped wear shown on the wall of the elbow [15].…”
Section: Analysis Of Wear Resultssupporting
confidence: 62%
“…This phenomenon occurs in both simulations and experiments. With further observation of the wear on the wall of the hub, we found that the wear surface had corrugated stripes, which were very similar to the striped wear shown on the wall of the elbow [15].…”
Section: Analysis Of Wear Resultssupporting
confidence: 62%
“…Particles and water return to the particle tank. Water enters the water tank (13) through the filter (12) and then returns to the circulation pipe line through the gate valve (17). When circulating piping is used, it is difficult to change the working condition of the pump.…”
Section: Experimental Devicementioning
confidence: 99%
“…The experimental results show that the random collision caused by the kinetic energy fluctuation of the solid phase is closely related to the wear of this region. Li et al simplified the impeller passage into a curved tube and studied the relationship between coarse particle motion and wall wear [17].…”
Section: Introductionmentioning
confidence: 99%
“…In process machinery, pumps, valves, pipes, absorption tower, fluid-bed and other devices which involve complex flow or heat transfer are indispensable [1][2][3][4][5][6][7][8][9][10][11][12][13]. Among them, the valve is an important controlling device for opening and closing pipelines, adjusting the flow direction and regulating the transmission of the medium [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%